Adenosine triphosphate bioluminescence to validate decontamination of endoscopes. Issue 4 (December 2017) - Gillespie, E.; Sievert, W.; Swan, M.; Kaye, C.; Edridge, I.; Stuart, R.L.
Summary: The reports of outbreaks involving carbapenemase-resistant Enterobacteriaceae (CRE) associated with gastrointestinal endoscopy prompted a review and study of a novel method of assessing cleaning. This study assessed adenosine triphosphate (ATP) bioluminescence to demonstrate cleanliness prior to endoscopy. ATP testing was compared with microbiological monitoring for 127 endoscopes. Samples were taken after cleaning, reprocessing and storage, but immediately before the endoscopy procedure. We recommend implementing ATP testing prior to endoscopy procedures as an alternative to microbiological testing at periodic intervals. ATP testing provides a convenient assessment of endoscopy hygiene to demonstrate safety and quality assurance.